UPAYA PENGENDALIAN BIAYA PRODUKSI UNTUK OPTIMALISASI LABA PERUSAHAAN PADA PT. PERKEBUNAN NUSANTARA IX KEBUN GETAS - Mahagiyani Mahagiyani; Dwi Aryani S; Vony Sevita Widasari (Pusat P2M Politeknik Negeri Batam, 2018)
Production cost is all expenses relating to production function or activities in processing raw material to be end products. Rubber Factory activities are aimed to gaining profit for the company, Kebun Getas, PT Perkebunan Nusantara IX. This research is intended to find out the effect of production cost increase toward the company profit, Kebun Getas, PT Perkebunan Nusantara IX, and its control in order to get the information on the total of production cost and profit in the last two years. The research methods used are descriptive, quantitative and verification methods. The result of the research shows that based on the cost structure analysis 2015 and 2016, the highest expense of production cost derives from the total of harvesting cost amounting to Rp. 18.625.174.605 or 68%, meanwhile in 2016 amounting to Rp. 15.607.846.234 or 63%.